Kepadatan Bakteri Total Dan Azotobacter sp Di Rizosfer Selada (Lactuca sativa L.) Setelah Aplikasi Kasing Dan Pupuk NPK - Maya Damayani; Reginawanti Hindersah; Yusuf Rahman (Agrologia, 2016)
Organic matter and inorganic fertilizer application are important to maintain the existence of potential microbes in the rhizosphere and maintain the soil quality. A greenhouse experiment has been carried out to determine the effect of  vermicompost and NPK fertilizer on total bacterial and Azotobacter  population in rhizosphere and yield of lettuce (Lactuca sativa L.) grown in soil order of  Inceptisols. The experimental design was a factorial randomized complete block design with three replicates were tested three doses of vermicompost (7.5, 15 and 22.5 t ha-1) and four doses of inorganic fertilizers; NPK (300; 450; 600 and 750 kg ha-1). The results showed that there was no significant interaction between vermicompost and NPK fertilizer on either total bacterial or Azotobacter population, as well as on fresh weight of lettuce. Both vermicompost and NPK fertilizer did not affect the biological parameters. However, the application of 750 kg/ha NPK fertilizer can increased lettuce weight up to 24% compared to that of control. This study suggested that in the relatively poor soil nutrients, lettuce growth was depend on inorganic fertilizers.